Food dry matter determination for animal use through microwave oven and Koster Tester - Godinho, Ricardo Ferreira; Carvalho, Rita de Cássia Ribeiro; Ferreira, Eliel Alves (Revista de Ciências Agroveterinárias, 2015)
Knowing the dry matter intake of an animal is the first step in formulating diets for dairy cows. There are a variety of equipments and methods which can be used for drying food; each type has advantages and disadvantages for using on the farm. The objective of this study was to identify and evaluate a methodology for assessing the moisture content and dry matter in animal food, feasible for adoption on farms. The Koster Tester and the microwave oven with and without the water container, usually recommended to avoid burning the sample, were used to determine the dry matter of the whole cornplant silage, wet corn grain silage and total mixed ration. In determining the dry matter of high moisture corn grain, the Koster was more accurate when compared to the microwave oven with or without water container. For samples of total mixed rationand whole corn plant silage, the microwave oven without the water container proved to be more effective, followed by Koster. The use of the microwave oven as a means of obtaining the dry matter content was more efficient than the use of Koster, being easier, practical and feasible for using on farms. Not using the water container made the microwave oven more effective and the burning of the sample was avoided through the use of materials without leaving a space at the center of the container with the sample.